Genome-wide Identification, Expression, and Functional Analysis of MdMSI Genes in Apples (Malus domestica Borkh.) - Wang, Daru; Wang, Xun; Zhang, Chunling; Yang, Kuo; Wang, Xinjie; Cui, Jianying; Liu, Dandan; You, Chunxiang (Frontiers in Genetics, 2022)
The multicopy suppressor of IRA (MSI) is a subfamily of WD40 repeat proteins, which is widely involved in plant growth and development. In order to explore the function of MdMSI members in abiotic stress, we identified 8 MSI gene family members from the Malus × domestica reference genome. They were distributed on 6 chromosomes, and they had similar secondary and tertiary structure. We found a variety of regulatory elements in response to hormones and abiotic stress in MdMSI promoters. Through qRT-PCR analysis, it was revealed that MdMSIs were expressed in all tissues, especially in roots. The analysis results also revealed that the expression of MdMSIs was induced in varying degrees under salt, drought stress and ABA treatments. Furthermore, we obtained overexpression of MdMSI1-1 transgenic apple calli and Arabidopsis. Overexpress of MdMSI1-1 in calli and Arabidopsis played a negative regulatory role in salt stress response. Our work laid a foundation for further verifying the function of MSI genes under abiotic stress in apple.